Risk Factors for The Incident of Serotinus Pregnancy in The Lalowaru Health Center Area, North Moramo District: Serotinus Pregnancy - Apriyanti; Nazaruddin; Dina, Hasniah; Krismiadi, Dedi (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Post-term pregnancy is one of the complications that can be detrimental to the mother and baby, one of which is a decrease in fetal weight which can cause death in the baby. Objective: To determine the risk factors for serotinus pregnancy in the Lalowaru Community Health Center area, North Moramo District. Methods: This type of quantitative analytical research uses a case-control design. The population in the study were all mothers with a history of serotinus pregnancy. The total sample was 66 respondents, using random sampling techniques Results: There were 32 respondents (48.5%) who were at risk of experiencing a serotinous pregnancy and 34 other respondents (51.5%) who were not at risk of experiencing a serotinous pregnancy. In addition, 31 respondents (47%) with parity were at risk of experiencing a serotinous pregnancy and 35 respondents (53%) were not at risk of experiencing a serotinous pregnancy. The results showed that respondents at risk age had a 31.006 times greater chance of experiencing a serotonin pregnancy and respondents in the risk category had a 17.031 times greater chance of experiencing a serotonin pregnancy. Based on the results of statistical tests, a ρ value of 0.003 (0.003<0.05) was obtained, indicating that age is a risk factor for serotinus pregnancy. The ρ value is 0.010 (0.010<0.05), which means that parity is also a risk factor for serotinus pregnancy. Conclusions: age and parity are risk factors for serotinous pregnancy in the Lalowaru Community Health Center Working Area, North Moramo District